2014
DOI: 10.1007/s10840-014-9900-4
|View full text |Cite
|
Sign up to set email alerts
|

Implanted endocardial lead characteristics and risk of stroke or transient ischemic attack

Abstract: Introduction Patent foramen ovale (PFO) has been recently implicated as a strong predictor of stroke or transient ischemic attack (TIA) in patients with implanted pacemaker or defibrillation leads. Leads in the right heart can form thrombi that embolize to the pulmonary circulation and raise pulmonary pressure. This increases right-to-left shunting through PFO or intrapulmonary shunts and can result in paradoxical embolism. We sought to determine whether certain lead characteristics confer a higher thrombogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…No clinically significant emboli were identified but that does not rule out silent thromboembolism in this retrospective study. It has previously been shown that passively fixated tined RA leads are associated with a higher risk of TIA [19]. In our study, there were no masses identified on passively fixated tined RA leads, and there was only one mass located on a passively fixated tined RV lead.…”
Section: Discussionsupporting
confidence: 38%
“…No clinically significant emboli were identified but that does not rule out silent thromboembolism in this retrospective study. It has previously been shown that passively fixated tined RA leads are associated with a higher risk of TIA [19]. In our study, there were no masses identified on passively fixated tined RA leads, and there was only one mass located on a passively fixated tined RV lead.…”
Section: Discussionsupporting
confidence: 38%
“…In addtion, she also has permenant pacemaker leads which may increase her risk for paradoxial embolism. 18 I would therefore consider percutaneous iASD closure in this patient. A suggested algorithm for the assessment and management of iASD is illustrated in Figure 3.…”
Section: 4-7mentioning
confidence: 99%
“…We obtained patients for this study from the population of patients with CIEDs and endocardial device leads reported in earlier studies on risk of stroke/TIA 2,6 and pulmonary embolism (PE). 17 Patients who underwent implantation of either transvenous ICD or pacemaker at the Mayo Clinic, Rochester, MN between January 1, 2000 and October 25, 2010 were included in this study if they were diagnosed with a definite PFO on echocardiography, and had a baseline (see below for definition of “baseline”) echocardiogram to obtain information on study predictors.…”
Section: Methodsmentioning
confidence: 99%